Platinum-nickel-phosphorus nano hexapod-nitrogen-doped graphene aerogel composite material as well as preparation method and application thereof
By using platinum-nickel phosphorus nanohexapod-nitrogen doped graphene aerogel composite as a catalyst in electrocatalytic hydrogen evolution reaction, the existing platinum precious metal catalysts have been solved, and high efficiency has been achieved , stable electrocatalytic hydrogen evolution performance.
Patent Information
- Application Number
- CN202411615299.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing electrocatalytic hydrogen evolution reaction, the high cost of platinum precious metal catalysts, insufficient catalytic activity and poor stability, limiting their wide application.
Platinum-nickel phosphorus nanohexapods-nitrogen doped graphene aerogel composite material as a catalyst, platinum-nickel nanohexapods were synthesized by hydrothermal method, and oxidation treatment and phosphorus doping were used to form high activity and stability catalyst.
The number and stability of the active sites of the catalyst are improved, the catalytic activity is enhanced, and the shedding of platinum-nickel nanohexapod particles and Ostwald maturation are avoided, achieving excellent electrocatalytic hydrogen evolution performance.
Smart Images

Figure CN119465266A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by hydrolysis, and specifically relates to a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is the backbone of energy transformation and the key to addressing global warming and issues related to traditional energy systems. Hydrogen is a clean energy with high energy density. The only product of its combustion is water, which is an ideal fuel for fuel cells. According to statistics, hydrogen has an amazing energy storage capacity, with about 120MJ of energy contained in each kilogram of hydrogen, which is twice that of most traditional materials. At the same time, compared with clean energy such as wind energy and solar energy, hydrogen can be stored in different forms (gas, liquid, metal hydride, etc.) to facilitate long-distance transportation. Since 1874, Jules Verne has recognized the limited supply of coal as an energy source and realized the possibility of producing hydrogen by water electrolysis, so he put forward the view that "water will be the coal of the future". Rudolf Erren suggested in the 1930s that the use of hydrogen produced by water electrolysis as a transportation fuel can reduce automobile exhaust emissions. Similarly, Francis Bacon also suggested the use of hydrogen as an energy storage system. In recent years, many countries have laid out corresponding industrial chains in the field of hydrogen energy and fuel cells. In 2017, the United Nations Bonn Climate Conference predicted that hydrogen energy will account for 20% of total energy consumption by 2050, and the future world cannot do without the use of hydrogen energy. Therefore, the development and large-scale production of hydrogen energy are of great significance.
[0003] In the current electrocatalytic hydrogen evolution reaction process, platinum noble metal catalysts are mainly used to drive it. However, the cost of noble metal platinum is high, platinum nanoparticles are easy to agglomerate, and problems such as Ostwald ripening and dissolution and shedding lead to insufficient catalytic activity and poor stability, which seriously limits the widespread application of platinum catalysts. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a new phosphating strategy, namely, a method for preparing a platinum-nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composite material. The prepared aerogel composite material can be used as an efficient catalyst in the field of hydrogen production by electrolysis of water.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material, the method comprising the following steps:
[0007] S1. dispersing graphene oxide in water, adding ascorbic acid, and obtaining reduced graphene oxide hydrogel after hydrothermal reaction;
[0008] S2, after exchanging water in the reduced graphene oxide hydrogel with an organic solvent, adding the reduced graphene oxide hydrogel into the same organic solvent containing platinum salt and nickel salt and soaking it for 1-3 days, then subjecting the mixture to a hydrothermal reaction, and obtaining platinum-nickel nanohexapod / nitrogen-doped graphene aerogel after washing and drying after the reaction;
[0009] S3. The platinum nickel nanohexapod / nitrogen-doped graphene aerogel is prepared into an oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel by oxidation treatment, and then the aerogel is placed in an inert gas range for heating treatment together with a phosphorus source, so as to finally obtain a platinum nickel phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material.
[0010] The present invention first prepares a reduced graphene oxide hydrogel, then introduces platinum nickel nanohexapods on a graphene aerogel with a rich pore structure by a hydrothermal method, then obtains a synthetically oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel by heating it in an air atmosphere, and finally heats it together with a phosphorus source in an argon atmosphere, and finally obtains a nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composite material with high activity and a special nanohexapod structure. Among them, the nanohexapod particles are uniformly dispersed in the nitrogen-doped graphene aerogel, which increases the number of catalyst active sites, increases the intrinsic catalytic activity of the catalytic active sites, stabilizes the particle structure, and improves the catalyst stability, and can be used as an efficient catalyst in the fields of water electrolysis and hydrogen production.
[0011] Preferably, in S1, the concentration of graphene oxide in water is 0.5-20 mg / mL, and the concentration of ascorbic acid is 10-50 mg / mL. More preferably, the concentration of graphene oxide in water is 5-15 mg / mL.
[0012] Preferably, in S1, the temperature of the hydrothermal reaction is 40-90° C. and the time is 1-5 h.
[0013] Preferably, in S2, the concentration of the platinum salt is 1-100 mmol / L, and the concentration of the nickel salt is 1-450 mmol / L. More preferably, the concentration of the platinum salt is 1-15 mmol / L, and the concentration of the nickel salt is 1-45 mmol / L.
[0014] Preferably, in S2, the temperature of the hydrothermal reaction is 50-240° C., and the time is 1-48 h.
[0015] Preferably, in S2, the organic solvent is selected from one or more of methylformamide, isopropanol, ethanol, methanol, acetone, tert-butanol, and ethylene glycol.
[0016] Preferably, in S3, the platinum nickel nanohexapod / nitrogen-doped graphene aerogel is placed in an air atmosphere for high-temperature oxidation treatment to form oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel, and the oxidation treatment temperature is 50-400° C. and the time is 1-4 hours.
[0017] Preferably, in S3, the phosphorus source is selected from one or more of hypophosphorous acid, phosphorous acid, hypophosphoric acid, sodium phosphate, sodium hypophosphite, sodium phosphite, and sodium hypophosphite.
[0018] Preferably, in S3, the mass ratio of the oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel to the phosphorus source is less than 1 / 10.
[0019] Preferably, in S3, the heating treatment is carried out at 100-200°C and 200-300°C for 1-3h each.
[0020] The second aspect of the present invention provides a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material prepared by the preparation method described in the first aspect.
[0021] The platinum nickel phosphorus nanohexapod-nitrogen doped graphene aerogel composite material prepared by the method of the present invention has a three-dimensional porous structure, the nitrogen doped graphene is used as a carrier, the platinum nickel bimetallic particles are nano hexapod structures, the phosphorus element is doped in the platinum nickel nanohexapod, and the size of the platinum nickel phosphorus nanohexapod does not exceed 8nm.
[0022] The third aspect of the present invention provides the use of the platinum nickel phosphorus nanohexapod-nitrogen doped graphene aerogel composite material described in the second aspect in hydrogen production by water electrolysis.
[0023] Preferably, the platinum nickel phosphorus nanohexapod-nitrogen doped graphene aerogel composite material is used as a catalyst for electrocatalytic hydrogen evolution.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention first synthesizes platinum nickel nano hexapod / nitrogen doped graphene hydrogel by a hydrothermal method, and the formation of small-particle platinum nickel nano hexapod can increase the number of active sites of the catalyst, and the uniform compounding of platinum nickel nano hexapod in nitrogen doped graphene aerogel further improves the stability of the catalyst, and avoids the shedding and Ostwald ripening of platinum nickel nano hexapod particles during long-term use. Then the platinum nickel nano hexapod / nitrogen doped graphene aerogel is placed in air for heating treatment to form oxidized platinum nickel nano hexapod / nitrogen doped graphene aerogel, which provides more binding sites for subsequent doping of phosphorus atoms. Finally, the oxidized platinum nickel nano hexapod / nitrogen doped graphene aerogel and the phosphorus source are heated in different zones, and finally a platinum nickel phosphorus nano hexapod / nitrogen doped graphene aerogel composite material is obtained. The prepared aerogel electrocatalyst has a hierarchical porous structure, which can fully expose the active sites to provide a fast material transfer channel. At the same time, phosphorus doping can well accelerate the rapid dissociation kinetics of water, thereby providing sufficient hydrogen ion supply and strong electronic coupling for optimal intermediate adsorption, thus giving the catalyst excellent comprehensive hydrogen evolution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Transmission electron microscope images of platinum nickel phosphorus nanohexapod / nitrogen-doped graphene aerogel composite materials; among them, a, d, g are PtNiNF-NGA, b, e, h are O-PtNiNH / NGA, c, f, i are P-PtNiNH / NGA.
[0027] Figure 2 The figures are a comparison of the hydrogen evolution performance of platinum-nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composites with different platinum-nickel ratios (1:1, 1:2, 1:3) and commercial Pt / C; Figure a is the linear sweep voltammetry (LSV) curve, and the electrocatalytic hydrogen evolution performance of samples with various reaction ratios is better than that of commercial Pt / C; Figure b is the Tafel slope, which reflects the electrocatalytic hydrogen evolution performance of samples with various ratios. The smaller the value of the Tafel slope, the more sensitive the reaction rate is to the change of the electrode potential, and the greater the change in the reaction rate, the better the performance.
[0028] Figure 3 Comparison of the chronopotentiometry curves of platinum-nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composites with different platinum-nickel ratios (1:1, 1:2, 1:3) and commercial Pt / C under constant current. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0031] Example 1: Preparation method of platinum nickel phosphorus nanohexapod-nitrogen doped graphene aerogel composite material
[0032] The specific preparation method comprises the following steps:
[0033] (1) Synthesis of uniform reduced graphene oxide hydrogel:
[0034] Graphene oxide was prepared by a modified Hummers method (the synthesis method can be referred to the literature "[1] Wang Lu. Preparation of graphene oxide by improved Hummers method and its characterization [J]. Journal of Packaging, 2015, 7(2): 5. DOI: 10.3969 / j.issn.1674-7100.2015.02.006."). 10 mL of about 15 mg / mL graphene oxide aqueous solution was added with 20 mg of ascorbic acid, ultrasonically homogenized, hydrothermally treated at 70 ° C for 3 h, and thoroughly washed with deionized water to obtain reduced graphene oxide hydrogel.
[0035] (2) Synthesis of Pt-Ni nanohexapod / nitrogen-doped graphene aerogel:
[0036] After exchanging the water in the prepared reduced graphene oxide hydrogel with isopropanol (pour out the water and add isopropanol), the reduced graphene oxide gel absorbed with isopropanol was added to 18mL isopropanol solution containing 10mmol / mL platinum acetylacetonate and 30mmol / mL nickel acetylacetonate and soaked for 2 days. Then the mixture was transferred to an autoclave for hydrothermal reaction at 200℃ for 24h. After the reaction was completed, it was thoroughly washed with anhydrous ethanol and deionized water in turn, and the obtained hydrogel was further washed with tert-butyl alcohol to obtain platinum nickel nanohexapod / nitrogen doped graphene gel, and finally freeze-dried to obtain platinum nickel nanohexapod / nitrogen doped graphene aerogel (Pt1Ni3NF-NGA).
[0037] (3) Synthesis of oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel:
[0038] The prepared platinum nickel nanohexapod / nitrogen-doped graphene aerogel was placed in a tubular furnace and treated at 150°C for 2.5 hours in an air atmosphere to obtain oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel (O-Pt1Ni3NH3 / NGA).
[0039] (4) Synthesis of Pt-Ni-P nanohexapod / nitrogen-doped graphene aerogel:
[0040] The prepared oxidized platinum nickel nanohexapod / nitrogen doped graphene aerogel and sodium hypophosphite were placed in a double hot zone tubular furnace with a mass ratio of oxidized platinum nickel nanohexapod / nitrogen doped graphene aerogel to sodium hypophosphite being 1:30. Then, they were treated at 150°C and 250°C for 2 h respectively under an argon atmosphere (flow rate of 10 mL / min) to obtain platinum nickel phosphorus nanohexapod / nitrogen doped graphene aerogel (P-Pt1Ni3NH3 / NGA).
[0041] Figure 1 The transmission electron microscope and scanning electron microscope images of the platinum nickel phosphorus nanohexapod / nitrogen-doped graphene aerogel composite material of Example 1 show that it has a three-dimensional continuous pore structure, and the platinum nickel phosphorus alloy has an obvious nanohexapod structure. At the same time, the platinum nickel hexapod particles exist in the form of small particles of about 7 nm and are attached to the graphene.
[0042] Example 2: A method for preparing a platinum-nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composite material
[0043] The method for preparing platinum nickel phosphorus nanohexapod / nitrogen-doped graphene aerogel in this embodiment is the same as that in Example 1, except that: in step (2), the water in the prepared reduced graphene oxide hydrogel is exchanged with acetone to prepare graphene acetone gel; 18 mL of isopropanol solution containing 10 mmol / mL platinum acetylacetonate and 30 mmol / mL nickel acetylacetonate is replaced with 18 mL of acetone solution containing 10 mmol / mL platinum acetylacetonate and 20 mmol / mL nickel acetylacetonate, and the synthesized platinum nickel nanohexapod / nitrogen-doped graphene aerogel is recorded as P-Pt1Ni2NH / NGA.
[0044] Example 3: A method for preparing a platinum-nickel-phosphorus nanohexapod / nitrogen-doped graphene aerogel composite material
[0045] The method for preparing platinum nickel phosphorus nanohexapod / nitrogen-doped graphene aerogel in this embodiment is the same as that in Example 1, except that: in step (3), 18 mL of isopropanol solution containing 10 mmol / mL platinum acetylacetonate and 30 mmol / mL nickel acetylacetonate is replaced by 18 mL of tert-butanol solution containing 10 mmol / mL platinum acetylacetonate and 10 mmol / mL nickel acetylacetonate, and the synthesized platinum nickel nanohexapod / nitrogen-doped graphene aerogel is recorded as P-Pt1Ni1NH / NGA.
[0046] Electrocatalytic hydrogen evolution tests were performed on the Pt-Ni-P nanohexapod / nitrogen-doped graphene aerogel composites obtained in Examples 1-3 (commercial Pt / C was used as a control). All electrochemical HER performances were performed in a N2-saturated three-electrode system, with a Pt (provided by P-PtNiNH / NGA) loading of approximately 9.1 μg / cm 2The rotating disk electrode (RDE, 5 mm), graphite rod and Hg / HgO (1 M KOH) were used as the working electrode, counter electrode and reference electrode. The P-PtNiNH / NGA of Examples 1-3 was measured to have lower overpotential and higher electrochemical stability than commercial Pt / C, showing high catalytic activity ( Figure 2 , Figure 3 ).in, Figure 2 Example 1 (P-Pt1Ni3NH / NGA), Example 2 (P-Pt1Ni2NH / NGA), Example 3 (P-Pt1Ni1NH / NGA) at 10 mA cm -2 The overpotential is lower than that of Pt / C. Figure 2 b reflects the Tafel slope of P-PtNiNH / NGA of Examples 1-3. The smaller the value of the Tafel slope, the more sensitive the reaction rate is to the change of the electrode potential. The greater the change in the reaction rate, the better the performance. It can be seen that the P-PtNiNH / NGA of Examples 1-3 are superior to commercial Pt / C. Figure 3 Reaction Examples 1, 2, and 3 at 10 mA cm -2 The stability under high temperature is much better than that of commercial Pt / C.
[0047] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material, characterized in that: The following steps are involved: S1. dispersing graphene oxide in water, adding ascorbic acid, and obtaining reduced graphene oxide hydrogel after hydrothermal reaction; S2, after exchanging water in the reduced graphene oxide hydrogel with an organic solvent, adding the reduced graphene oxide hydrogel into the same organic solvent containing platinum salt and nickel salt and soaking it for 1-3 days, then subjecting the mixture to a hydrothermal reaction, and obtaining platinum-nickel nanohexapod / nitrogen-doped graphene aerogel after washing and drying after the reaction; S3. The platinum nickel nanohexapod / nitrogen-doped graphene aerogel is prepared into an oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel by oxidation treatment, and then the aerogel is placed in an inert gas range for heating treatment together with a phosphorus source, so as to finally obtain a platinum nickel phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material.
2. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S1, the concentration of graphene oxide in water is 0.5-20 mg / mL, and the concentration of ascorbic acid is 10-50 mg / mL.
3. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S2, the concentration of platinum salt is 1-100 mmol / L, and the concentration of nickel salt is 1-450 mmol / L.
4. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S2, the organic solvent is selected from one or more of methylformamide, isopropanol, ethanol, methanol, acetone, tert-butanol, and ethylene glycol.
5. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S3, the platinum nickel nanohexapod / nitrogen doped graphene aerogel is placed in an air atmosphere for high temperature oxidation treatment to form oxidized platinum nickel nanohexapod / nitrogen doped graphene aerogel, and the oxidation treatment temperature is 50-400° C. and the time is 1-4 hours.
6. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S3, the phosphorus source is selected from one or more of hypophosphorous acid, phosphorous acid, hypophosphoric acid, sodium phosphate, sodium hypophosphite, sodium phosphite, and sodium hypophosphite.
7. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S3, the mass ratio of the oxidized platinum nickel nanohexapod / nitrogen-doped graphene aerogel to the phosphorus source is less than 1 / 10.
8. The method for preparing a platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 1, characterized in that: In S3, the heating treatment is carried out at 100-200°C and 200-300°C for 1-3h each.
9. A platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the platinum-nickel-phosphorus nanohexapod-nitrogen-doped graphene aerogel composite material according to claim 9 in hydrogen production by water electrolysis.